Kształtowanie kompetencji emancypacyjnych w Salach Doświadczania Świata. Idea Snoezelen i jej wyjście naprzeciw potrzebom podopiecznego - Bagińska, Paula (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2016)
In this article the author illustrates an idea of Snoezelen (Multisensory Environments, polish: Sala Doświadczania Świata), while describing its potential for stimulating self-awareness and autonomy of its users. She analyses the main motives of creators of Snoezelen, to expose the influence of their attitudes towards an importance of basic human rights of people with every disability level on contemporary popularity and usefulness of Snoezelen for variety of recipients. She then examines the meaning of each of the main principles of Snoezelen Room, to hightlight a connection between Snoezelen and the development of independence and self-esteem of its users. The conclusion of this analysis, as well as a personal experience of the author in using the Snoezelen method, allowed to frame an idea of the process of gaining individual autonomy in the environment of Snoezelen Room.